Soil carbon dioxide efflux and atmospheric impact in a 10 years Dipterocarpus recovering lowland tropical forest, Peninsular Malaysia - Mande, Hosea Kato; Abdullah, Ahmad Makmom; Aris, Ahmad Zaharin; Nuruddin, Ahmad Ainuddin (Springer, 2013)
Recovering logged-over forest ecosystem increases CO2 efflux into the atmospheric carbon pool in response of environmental factors to change in soil temperature and moisture. These CO2 outbursts can have a marked influence on the ecosystem carbon balance and thereby affect the atmospheric carbon pool. The study was conducted in a 10 years logged-over forest of Sungai Menyala forest, Port Dickson, Negeri Sembilan, Malaysia. The measurements of soil CO2 effluxes were conducted using a continuous open flow chambers technique connected to a multi gas-handling unit and infrared CO2/H2O gas analyser. The aim of this study is to determine the percentage of CO2 contributed into the atmosphere from a recovering 10 year logged-over lowland forest. One-way analysis of variance (ANOVA) was used to test the significance correlation between soil CO2 efflux and environmental variables. Post-hoc comparisons were made using Tukey test (p < 0.05), and multiple linear regressions were used to determine the impact of environmental factors on soil CO2 efflux. Soil CO2 efflux range from 345.6 to 600.4 mg/m−2/h−1 with the highest efflux in the afternoon attributed to increase in soil temperature and moisture. Higher soil temperature and moisture recorded signify the influential factor. Furthermore, the predictor environmental variables; Soil Organic Carbon (SOC), Total Organic Carbon (TOC), Soil Moisture Content (SMC), Bulk Density, Below Ground Carbon Stock, Total Aboveground Carbon Biomass (TAGB), soil pH, Nitrogen to Carbon ratio account for the spatial and temporal variation in soil CO2 efflux. These factors attributed to increase in CO2 efflux into the atmosphere.